Research on RF Environment Simulation in KD-JMASE. Issue 3 (April 2019) - Yang, Zhonghua; Li, Ge; Wang, Peng; Zhang, Xiang
Abstract: KD-JMASE is a supporting environment for modeling and simulation. It is a set of standards services and application programming interfaces. It provides the simulation of RF environment to calculate the superposition effect of electromagnetic wave signal in the process of transmitting and receiving. Reproduce the transmission process of scattering, diffraction, refraction and absorption of actual signals in real environment. This paper mainly studies the framework of RF environment simulation and the basic principles of simulation in KD-JMASE. The class structure design of RF environment effect model and the design of external communication port and the realization of actor-object cooperation in environment simulation are introduced in detail and design a simulation scenario to verify the atmospheric effect model in the RF environmental effect model.